Hospital discharge communication problems in 10 high-income nations: a secondary analysis of an international health policy survey - Neil J MacKinnon; Preshit Nemdas Ambade; Zach Hoffman; Kaamya Mehra; Munira Gunja; Breagh H MacKinnon; Minseo Yi (BMJ Open)
Objectives We aimed to determine the prevalence of hospital discharge communication problems in adults of 10 high-income nations and the associated factors.Design Secondary analysis of cross-sectional survey data.Setting 2023 Commonwealth Fund International Health Policy Survey for Adults, including data from residents of Australia, Canada, France, Germany, the Netherlands, New Zealand, Sweden, Switzerland, the UK and the USA.Participants 3763 survey respondents aged 18 and older who reported hospitalisation at least one time in the past 2 years.Primary and secondary outcome measures Our primary outcome measure is poor discharge communication (PDC), which is a composite variable comprising three questions regarding the provision of written information, follow-up arrangement and discussion of medications at time of discharge.Results The overall PDC rate was 17.1%, with the highest in Germany (19.7%) and the lowest in the Netherlands (9.2%). No follow-up arrangement was the most commonly reported problem (22.8%). Respondents who concerned about social service needs and mental health issues were more likely to report PDC.Conclusions Providers should consider factors which impact PDC at hospital discharge and tailor communication appropriately. Hospitals, communities and countries should work towards policies that address underlying issues related to social determinants of health, including support for lower-income patients, improved treatment access for patients with physical and mental health conditions, and food and housing stability.